PENGUATAN KEMAMPUAN KOMUNIKASI SOSIAL BUDAYA KELOMPOKTANI DESA PAKUBEUREUM - Syamsuddin Amin, Ali (JURNAL PARAHITA ABDIMAS: Jurnal Pengabdian Masyarakat, 2020)
Farmer groups are formed on the basis of the wishes of farmers facilitated by the relevant the institution, one of the benefits is to increase its capacity to become an economic institution of farmers. The problems faced, operationally there are weaknesses in the ability of socio-cultural communication, so that communication is less effective. Therefore, community service activities on the topic of strengthening the ability of social and cultural communication for farmers in the Pakubeureum Village are relevant to what is needed aimed at improving the ability of farmer groups to achieve their visions and missions. The method used is Participatory Rural Appraisal (PRS), with three stages of strengthening capabilities through socialization, practice, and evaluation. From the results of the evaluation, both the implementation of the service and the practice of strengthening capabilities qualitatively succeeded well and it can be concluded that the ability of social communication and cultural groups can be improved through strengthening programs.